Correlation between working positions and lactic acid levels with musculoskeletal complaints among dentists - Fiory Dioptis Putriwijaya; Titiek Berniyanti; Indeswati Diyatri (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Musculoskeletal complaints have been common for dentists since their body is unknowingly often in inappropriate positions when caring for patients. For example, they bend towards patients, suddenly move, and then rotate from one side to another. The repetitive movements are done in long term. High activities and sufficient recovery time can cause a buildup of lactic acid in their blood leading to obstruction of the energy intake from the aerobic system in their muscle cells, resulting in fatigue. As a result, such conditions trigger decreased muscle performances. Purpose: This study aimed to determine the correlation between working positions and lactic acid levels with the risk of musculoskeletal disorders among dentists at Public Health Centers in Surabaya. Method: This research was an analytical observational research using cross sectional approach. Sampling technique used in this research was cluster random sampling with nineteen samples. To evaluate the working positions of those samples, a rapid entire body assessment (REBA) method was used. Meanwhile, to observe the musculoskeletal disorders of those samples, a Nordic body map was used. Data obtained then were analyzed using Pearson correlation test with a significance level (p<0.05). Result: Results of data analysis using the Pearson correlation test showed that the significance value obtained was 0.036. It indicates that there was a correlation between the working positions and the lactic acid levels with the musculoskeletal disorders in those dentists. The results of the Pearson correlation test also revealed that there was a correlation between the working positions and the lactic acid levels among those dentists with a significance value of 0.025. Conclusion: It may be concluded that the wrong body positions during working can increase lactic acid level in the body of dentists. The increased level of lactic acid then can affect their muscles, leading to the high risk of musculoskeletal disorders.